Sediment-Hosted Lead-Zinc Deposits: The Existence in Indonesia - S. Digdowirogo; S. Prihatmoko; H. Lubis (Berita Sedimentologi, 2000)
The best known Pb-Zn-(Au-Ag) deposits and occurrences in Indonesia such as Gunung Limbung-West Java, Tanjung Balit-Riau and Paleleh-North Sulawesi are believed to be epigenetic or intrusive-related and chiefly hosted by volcanic and intrusives. None of them is of economic interest, and this deposit type makes an insignificant contribution to the world Pb-Zn reserves. By contrast, the sediment-hosted Pb-Zn-Ag deposits play an important role as they contribute more than two third of world Pb-Zn reserves.Sedex, which is one class of the sedimen-hosted Pb-Zn-Ag deposits, has recently been identified in the Herald Resources Ltd - PT Aneka Tambang Persero (Tbk) joint venture area, in the Sopokomil prospect, Dairi, North Sumatra during a drilling campaign. The sediment-hosted Pb-Zn deposit has actually been defined in Kelapa Kambit, Belitung.